Employees’ perceptions regarding the provision of a hybrid employee assistance programme: a case study of the Gert Sibande Department of Social Development (Mpumalanga) - Hlatshwayo, Sindile Goodnecia (My University, 2021)
Employee assistance programmes (EAPs) are workplace-based programmes that have grown significantly over the years, both domestically and abroad. The research study supported by literature in the field noted the importance of EAPs in enhancing employees‟ abilities to perform at their optimum level, as work performance may be constrained by some personal or work-related issues. This research study emerged within a context of a lack of empirical data on EAPs, particularly in the public sector. Amongst the contributing challenges that employees may encounter when trying to balance work and private life, the prevalence of several epidemics such as HIV and AIDS, tuberculosis (TB), mental health illnesses/disorders such as depression, stress and recently the coronavirus pandemic need to be considered. Against this backdrop, the research study explored managerial and non-managerial employees‟ perceptions regarding the provision of a hybrid EAP within the Gert Sibande Department of Social Development (DSD) (Mpumalanga). The data set for this research study was made of a non-probability sample of managerial and non-managerial employees from the Gert Sibande DSD. The research study adopted a qualitative research approach and an exploratory case study design. Data were collected using face-to-face interviews guided by two interview schedules. The findings provide insights regarding possible EAP aspects that need to be adapted for the DSD EAP to thrive. The predominant issues that emerged from the thematic analysis of the data included i) a lack of awareness regarding the existence of the programme and its policies, ii) poor marketing and communication of the programme, iii) poor visibility associated with geographic location as well as marketing and education, iv) poor utilisation and other factors. The main conclusion drawn from this study was that there seems to be a misalignment between theory and practice as far as EAPs are concerned. The DSD would have to reconsider its EAP and ensure that it is aligned to best practices and professional standards for it to be fully efficient. The research study culminates with suggestions for the DSD and future research.
A research project submitted in partial fulfilment of the requirements for the degree Master of Arts in Social Work to the Faculty of Humanities, School of Human and Community Development, University of the Witwatersrand, 2021